Walt Whitman and the American Civil War: from Wound Dresser to Good Gray Poet - Lindeen, Karilyn (Kansas State University, 2016)
Today, Walt Whitman is considered a famous nineteenth-century American poet. At the outbreak of the American Civil War however, he was underrated and underappreciated by American readers. Three editions of his book of poetry, Leaves of Grass, were not received well by American readers and his future in writing looked bleak. This was despite the fact that Whitman’s literary friend, Ralph Waldo Emerson, wrote an encouraging review of the first edition, which Whitman included in the second and third iterations. Ironically, Whitman’s career made a turn for the better when his brother, George Washington Whitman, was reported to be among the wounded or killed in the Battle of Fredericksburg on December 13, 1862. A dedicated family man, Whitman immediately boarded a train in New York and headed for Falmouth, Virginia, to check on his brother’s wellbeing. Whitman visited several makeshift hospitals before coming across Chatham Mansion, the temporary Union Hospital Headquarters. He saw at the base of a tree a pile of human limbs that had been tossed out of a first floor window following amputations. The scene was horrific and he paused to record what he saw in his diary. This experience forever changed Whitman the man and Whitman the poet and the transformation was evident in his subsequent writing, as Whitman first took on the persona of what I have designated as the Wound Dresser and years after the war the Good Gray Poet. This evolution changed the public perception of Whitman, and it occurred in phases. The initial phase was before the war, his work was considered obscene among American society due to his previous publications. The second transformation in Whitman was initiated by fear of personal loss when his brother was listed among the wounded and dead at Fredericksburg and the sight of the amputated limbs at Chatham Mansion. Had Whitman been exposed to the war slowly over time, the effect might not have been so profound, but Chatham was an earth shattering event in his life, as he admitted. The third phase was the result of daily exposure for years to the wounded and dying in the hospitals. He developed a personal connection with the men and was determined to stay with them, despite direct orders from hospital doctors that he should return home for his own physical and emotional recovery. His experience in the hospitals had transformed from a middle aged healthy man to a frail and brittle shell, evident in photographs of him during these years. The final phase was marked by the transformation in his writing. It was in this phase that Whitman created the most memorable and remarkable Civil War poetry that is still celebrated today. It was this poetry that caused American’s to revere him as the “Good Gray Poet.”
Keywords: Walt Whitman; History; Memory; Poetry; American Civil War; Good Gray Poet